2017
DOI: 10.1038/s41598-017-02838-2
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 receptor signalling promotes β-cell glucose metabolism via mTOR-dependent HIF-1α activation

Abstract: Glucagon-like peptide-1 (GLP-1) promotes insulin secretion from pancreatic β-cells in a glucose dependent manner. Several pathways mediate this action by rapid, kinase phosphorylation-dependent, but gene expression-independent mechanisms. Since GLP-1-induced insulin secretion requires glucose metabolism, we aimed to address the hypothesis that GLP-1 receptor (GLP-1R) signalling can modulate glucose uptake and utilization in β-cells. We have assessed various metabolic parameters after short and long exposure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 48 publications
5
54
0
Order By: Relevance
“…However, pretreatment with rhGLP‐1 obviously resulted in the upregulation of EAAT2 expression, indicating that rhGLP‐1 might play a key role in protecting neuronal cell from ischemia‐induced death by resistance to glutamate excitotoxicity. Recent a research confirmed that GLP‐1R signaling promotes β‐cell glucose metabolism via mTOR‐dependent hypoxia‐inducible factor 1 alpha activation (Carlessi et al, ), we will confirm the relationship between oxidative stress, m‐TOR signaling, and EAAT2 in future studies.…”
Section: Discussionsupporting
confidence: 63%
“…However, pretreatment with rhGLP‐1 obviously resulted in the upregulation of EAAT2 expression, indicating that rhGLP‐1 might play a key role in protecting neuronal cell from ischemia‐induced death by resistance to glutamate excitotoxicity. Recent a research confirmed that GLP‐1R signaling promotes β‐cell glucose metabolism via mTOR‐dependent hypoxia‐inducible factor 1 alpha activation (Carlessi et al, ), we will confirm the relationship between oxidative stress, m‐TOR signaling, and EAAT2 in future studies.…”
Section: Discussionsupporting
confidence: 63%
“…Our findings are not necessarily in dispute with the recent demonstration that GLP1 augments LC3II accumulation due to glucolipotoxicity (25), because the mechanism of action was not addressed in that study, and so might be independent of cAMP. Other data showing that GLP1 activates both mTORC1 (66) and AMPK (67) would also seem to exclude these protein kinases, suggesting that the mechanism linking GLP1 with autophagy in ␤-cells is likely to be unusual. It is probably also context dependent, because GLP1 inhibits LC3II accumulation due to tacrolimus dosing (68) in contrast to the situation with glucolipotoxicity (25).…”
Section: Discussionmentioning
confidence: 99%
“…Many of GSISmodulating inputs are mediated by G proteincoupled receptors (GPCRs). For example, receptors of glucagon-like peptide GLP-1 promote GSIS via activation of Gs and the corresponding rise in cAMP (6,7). Receptors of vasopressin and adenosine promote GSIS via activation of Gq (8)(9)(10).…”
mentioning
confidence: 99%